Analisis Stakeholder dalam Perumusan Peraturan Daerah tentang Pemenuhan Hak-hak Penyandang Disabilitas di Kabupaten Bojonegoro - Rahma Putri, Septia; Taufiq, Ahmad; Junadi, Junadi (Jurnal Ilmiah Administrasi Publik, 2024)
Every person with a disability has the same rights as everyone else. This right is guaranteed in every regulation including local regulations. Unfortunately, the formulation of regulations often encounters obstacles due to various interests of both policy makers or stakeholders in its preparation. The main focus in this research is on analyzing the role of stakeholders in the formulation of Regional Regulation Number 2 of 2021 using the Eden & Ackermann Power vs Interest Model analysis. This research uses data analysis techniques using the Miles & Huberman method, which consists of data reduction, data presentation and conclusion drawing. The Descriptive Qualitative approach used in this research aims to describe the role of stakeholders systematically and accurately in accordance with the actual situation. The stakeholders involved consist of the Bojonegoro Regency DPRD, Bojonegoro Regency Social Service, Bojonegoro Regency Disability Association (PDKB) and IDFos Indonesia. To analyze the role of stakeholders consists of three steps, namely Stakeholder Identification, Stakeholder Classification and Inter-Stakeholder Relationships. The results of this study show that stakeholder involvement in the formulation of Regional Regulations on the Fulfillment of the Rights of Persons with Disabilities is pseudo (not procedural). Stakeholder involvement in the formulation of the Regional Regulation only reached the Focus Group Discussion (FGD) stage, the rest were not involved. The lack of involvement is due to the lack of openness or transparency between stakeholders, making this Regional Regulation seem like a mere formality.